Political brand architecture: Towards a new conceptualisation of political branding in an emerging democracy. Issue 3 (2nd July 2016) - Mensah, Kobby
ABSTRACT: Political branding is an essential part of our electoral process. In the literature, some argue for political brand management based on policy attributes, others regard candidate attributes as the essential source, with the party brand mostly relegated to the background. This study argues that current approaches would result in parties being less responsive to the realities of electioneering campaigns. The objective is to understand how three political elements – party, candidate and policy – are managed to build a comprehensive political brand capable of reaching target voters. This case study focuses on a 2000 election campaign in Ghana. Data were collected via analyses of media items, in-depth interviews and focus group discussions. The findings suggest that party, candidate and policy attributes broaden a party's reach of target voters. The study proposes the concept of 'political brand architecture (PBA)' for effective political brand management.